2017
DOI: 10.5614/ejgta.2017.5.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Open-independent, open-locating-dominating sets

Abstract: A distinguishing set for a graph G = (V, E) is a dominating set D, each vertex v ∈ D being the location of some form of a locating device, from which one can detect and precisely identify any given "intruder" vertex in V (G). As with many applications of dominating sets, the set D might be required to have a certain property for D , the subgraph induced by D (such as independence, paired, or connected). Recently the study of independent locating-dominating sets and independent identifying codes was initiated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Open-independent, open-locating-dominating sets were first studied by Seo and Slater [33] who stated necessary and sufficient conditions for the existence of an OLD oind -set in a graph G that has girth g(G) ≥ 5.…”
Section: Complexity Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Open-independent, open-locating-dominating sets were first studied by Seo and Slater [33] who stated necessary and sufficient conditions for the existence of an OLD oind -set in a graph G that has girth g(G) ≥ 5.…”
Section: Complexity Resultsmentioning
confidence: 99%
“…For general graphs (with arbitrary girth), the conditions stated in Theorem 2. Seo and Slater [33] presented some results about OLD oind -sets in trees. The authors showed that every leaf and its neighbor are contained in any OLD oind -set of any tree T , if T has such a set.…”
Section: Complexity Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In societies, persons with nearly equal statuses tend to be friendly. For more details on the domination refer [6,7,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…There are several modifications on domination concept in graph. Some of them are locatingdominating set [2,6,19,23], independent dominating set [4,14], Roman dominating set [9,13]. In this paper, we are interested to study another variant of domination in graph, namely geodeticdominating set.…”
Section: Introductionmentioning
confidence: 99%